The hydrogen-free circumstellar interaction in the Type Ib supernova 2021efd: A clue to the mechanism of the helium-layer stripping - Pyykkinen, N.; Nagao, T.; Kuncarayakti, H.; Stritzinger, M. D.; Kangas, T.; Maeda, K.; Chen, P.; Sollerman, J.; Burns, C.; Bose, S.; Folatelli, G.; Ferrari, L.; et al. (EDP Sciences, 2026)
Context
Stripped-envelope supernovae (SESNe), including Type IIb, Ib, and Ic supernovae (SNe), originate from the explosions of massive stars whose outer envelopes have been largely removed during their lifetimes. The main stripping mechanism for the hydrogen (H) envelope in the progenitors of SESNe is often considered to be interaction with a binary companion, but the stripping mechanism for the helium (He) layer is unclear.
Aims
We study the process of the He-layer stripping in the progenitors of SESNe. This is closely related to the origin of their diverse observational properties.
Methods
We conducted photometric and spectroscopic observations of the Type Ib SN 2021efd, which shows signs of interaction with H-free circumstellar material (CSM). At early phases, its photometric and spectroscopic properties resemble those of typical Type Ib SNe. Around 30 days after the r-band light curve (LC) peak until at least ∼770 days, the luminosity of the multiband LCs is higher than that of regular SESNe and has at least three distinct peaks. The LC evolution is similar to that of SN 2019tsf, whose previously unpublished spectrum at 400 days is also presented here. The nebular spectrum of SN 2021efd shows narrow emission lines (∼1000 km s−1) in various species, such as O I, Ca II, Mg II, He I, [O I], [Ca II], and [S II]. Based on the observations, we studied the properties of the ejecta and CSM of SN 2021efd.
Results
Our observations suggest that SN 2021efd is a Type Ib SN that interacts with the CSM with the following parameters: The estimated ejecta mass, explosion energy, and 56Ni mass are 2.2 M⊙, 9.1 × 1050 erg, and 0.14 M⊙, respectively, and the estimated CSM mass, composition, and distribution are at least a few times 0.1 M⊙, H free, and clumpy, respectively. Based on the estimated ejecta properties, we conclude that this event is a transitional SN whose progenitor was experiencing He-layer stripping at the epoch of the explosion and was on the way to becoming a carbon-oxygen star (as the progenitors of Type Ic SNe) from a He star (as the progenitors of Type Ib SNe). The estimated CSM properties suggest that the progenitor had some episodic mass ejections at a rate of ∼5 × 10−3 − 10−2 M⊙ yr−1 for the last decade and slightly lower before this final phase at least from ∼200 years before the explosion for the assumed CSM velocity of 100 km s−1. For the case of ∼1000 km s−1, the necessary mass-loss rate would be higher by a factor of ten, and the timescales would be shorter by a factor of ten.